ASPECT VERBAL, PSYCHOGÉNÈSE ET ENSEIGNEMENT DU TEMPS EN FRANÇAIS - GENESTE, Philippe (Studia Universitatis Babeș-Bolyai Philologia, 2019)
Verbal Aspect, Psychogenesis and Tense Teaching in French. This article comes from a teacher’s observation: the failure to teach the French conjugation and the verbal forms. On the other hand, teaching leaves out the distinction between the unaccomplished aspect and the accomplished aspect of the verb, which forms the basis of the distinction between simple and compound tenses. However, the psychogenesis of verbal tenses shows us that aspect is the linguistic mirror of the time of the action and the linguistic crucible of the time representation of an epoch. Only the constructivist approach, which joins Jean Piaget’s genetic psychology and Gustave Guillaume’s psychosystems of language, allows a new proposal on the teaching of tense and conjugation in French, one that responds to the child’s development and to the way he/she constructs his/her own mother tongue. REZUMAT. Aspectul verbal, psihogeneza și predarea timpului verbal în limba franceză. Acest articol s-a născut din observațiile unui dascăl privind eșecul predării conjugării verbale și a formelor verbale în școlile franceze. Pe de altă parte, acest mod de predare omite distincția dintre aspectele perfect și imperfect ale verbului, care stă la baza contrastului dintre timpurile simple și timpurile compuse. Psihogeneza timpurilor verbale ne arată că aspectul este reflexia lingvistică a timpului acțiunii și creuzetul lingvistic al reprezentării timpului într-o epocă. Numai abordarea constructivistă, ce îmbină psihologia genetică a lui Jean Piaget și psihosistemele lingvistice ale lui Gustave Guillaume, permite o nouă propunere privind predarea timpurilor și conjugărilor verbale în limba franceză, propunere ce corespunde nivelului de dezvoltare a copilului și modului în care acesta își construiește propria limbă maternă. Cuvinte cheie: adaptare, achiziție, aspect, asimilare, cronogeneză, învățare, verb.